Systemic innate and adaptive immune responses to SARS-CoV-2 as it relates to other coronaviruses - Patrick O'Connell; Yasser A. Aldhamen (Taylor & Francis Group, 2020)
The deadly pandemic caused by the novel coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) represents one of the greatest threats humanity has faced in the last century. Infection with this easily transmissible virus can run the gamut from asymptomatic to fatal, and the disease caused by SARS-CoV-2 has been termed Coronavirus Disease 2019 (COVID-19). What little research that has already been conducted implicates pathological responses by the immune system as the leading culprit responsible for much of the morbidity and mortality caused by COVID-19. In this review we will summarize what is currently known about the systemic immune response to SARS-CoV-2 and potential immunotherapeutic approaches.